Lean: it’s not rocket science, it’s work science - Gaudet, Joanne; Bergeron, France (Université d'Ottawa | University of Ottawa, 2016)
The main goal of this paper is to deepen understanding for Lean as a science of work based on flow. Flow here is the process of energy moving through a system. The paper first presents the three main elements of a science. It then deals with internal consistency for Lean as a scientific knowledge system with a need to discard the notion of ‘truth’. Third, the paper delves into Lean as collaborative science. Finally, focus shifts to individual and team flow and how a Lean culture creates the conditions and relations for optimal individual and team flow for increased creativity and innovation. The authors conclude that a deeper understanding of Lean can help more organizations prosper.
Keywords: Lean; Lean as science; Collaborative science; Science of work; Toyota Production System; Process Improvement; Flow; Lean Leadership; Continuous Improvement; Teamwork; Efficiency; Effectiveness; Innovation; Organizational Culture; Organizational Development; PDSA; Problem solving